Assessment of the Behaviour of Flysch Rock Mass During Tunnel Boring in the Primary Lining Using Indicators and Limit Values of Displacements and Deformations - Tajduś, Antoni; Tajduś, Krzysztof (Archives of Mining Sciences, 2022)
The article describes the behaviour of the flysch rock massif (Carpathian flysch) during the drilling of three tunnels in the preliminary lining. These tunnels were excavated in: “Naprawa”, “Laliki”, and “Świnna Poręba”. The distance between these tunnels in a straight line was 50 km to 90 km. The results of the displacement of the contours of these tunnels and their convergence were analysed in detail. These values were compared with the indices used to assess the behaviour of the rock mass in the tunnel environment (Zasławski index and Hoek index) and the adopted limit values of displacements and deformations. On this basis, a critical analysis of the selection of initial supports in the completed tunnels was made, showing errors at the design stage.
Keywords: tunnels; preliminary lining of tunnels; assessment of flysch rock massifs; Hoek; Zasławski; Sakurai